Biocleaning of historical metal artworks: innovative green gels amended with microbial derivatives - Passaretti, Arianna; Cuvillier, Luana; Guilminot, Elodie; Sciutto, Giorgia; Joseph, Edith (Frontiers in Materials, 2023)
The research study is aimed to design innovative bio-gel formulations able to tackle altered historical metal artworks in a green and sustainable perspective. The target of the research is the removal of undesired or altered materials of both inorganic (i.e., corrosion and tarnishing) and organic nature (i.e., protective coatings). The designed gel systems are initially assessed on mock-ups. Iron-, copperand silver-based substrates, chosen as mostly present in historical metal collections, are chemically aged to form corrosion on the surface. Alternatively, they are coated with organic protectives (i.e., acrylic and nitrocellulose varnish) that are mostly used for indoor metal care. After multi-modal analytical assessment to check the action and safety of the gels on the metal mock-ups, the developed solutions are applied on real cases, thanks to the strong and fruitful collaboration with curators and conservators of metal artworks.